Association of hypovitaminosis D with triceps brachii muscle fatigability among older women: Findings from the EPIDOS cohort. (May 2018) - Duval, G.; Rolland, Y.; Schott, A.M.; Blain, H.; Dargent-Molina, P.; Walrand, S.; Duque, G.; Annweiler, C.
Highlights: Vitamin D is involved in musculoskeletal health. We found that lower 25OHD concentrations were associated with greater muscle fatigability in older women. This effect may underlie the involvement of vitamin D in physical performance and fall risk. Future analyses should examine the effects of vitamin D supplementation on the ability of muscles to exert effort over time. Abstract: Background: Vitamin D affects physical performance in older adults. Its effects on muscles, notably on muscle strength, remain unclear. The objective of this cross-sectional study was to determine whether hypovitaminosis D is associated with triceps brachii muscle fatigability in community-dwelling older women. Methods: A randomized subset of 744 women aged ≥75years from the EPIDOS cohort was categorized into two groups according to triceps brachii muscle fatigability, defined as loss of strength >5% between two consecutive maximal isometric voluntary contractions. Hypovitaminosis D was defined using consensual threshold values (i.e., serum 25-hydroxyvitamin D concentration [25OHD] ≤10 ng/mL, ≤20 ng/mL, and ≤30 ng/mL). Age, body mass index, comorbidities, use psychoactive drugs, physical activity, first triceps strength measure, hyperparathyroidism, serum concentrations of calcium, albumin and creatinine, season and study centers were used as potential confounders. Results: The prevalence of hypovitaminosis D ≤ 30 ng/mL was greater among women with muscle fatigability compared with the others (P = .009). There was no between-group difference using the other definitions of hypovitaminosis D. The serum 25OHD concentration was inversely associated with the between-test change in triceps strength (adjusted β = −0.09 N, P = .04). Hypovitaminosis D ≤ 30 ng/mL was positively associated with triceps fatigability (adjusted OR = 3.15, P = .02). Conclusions: Vitamin D concentration was inversely associated with the ability to maintain strength over time in this cohort of community-dwelling older women. This is a relevant new orientation of research toward understanding the involvement of vitamin D in muscle function.